A case of VEXAS syndrome (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) with decreased oxidative stress levels after oral prednisone and tocilizumab treatment - Tozaki, Nagie; Tawada, Chisato; Niwa, Hirofumi; Mizutani, Yoko; Shu, En; Kawase, Aki; Miwa, Yuki; Ohnishi, Hidenori; Sasai, Hideo; Miyako, Keisuke; Hosokawa, Junichi; Kato, Ayaka; et al. (Frontiers in Medicine, 2022)
VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome has recently been described as an autoinflammatory disease associated with severe adult-onset inflammatory manifestations. The various clinical manifestations include recurrent high-grade fever, neutrophilic dermatoses, cutaneous vasculitis, chondritis of the ear and nose, pulmonary infiltrates, cytopenia, uveitis, gastrointestinal pain or inflammation, aortitis, hepatosplenomegaly, and hematological disorders. VEXAS syndrome is caused by somatic mutations of the ubiquitin-like modifier activating enzyme 1 (UBA1) gene in myeloid-lineage cells. It is characterized by vacuolated myeloid and erythroid progenitor cells seen by bone marrow biopsy. We report the case of a 64-year-old Japanese man with VEXAS syndrome. At age 63, he was referred to us with a recurrent erythema on the hands associated with a general fever of 38–40°C that had persisted for 4 or 5 days and had recurred about once a month for a year. The skin rash appeared 2 or 3 days after the onset of each fever episode. Computed tomography (CT) of the chest revealed bilateral hilar lymphadenopathy (BHL), and the mediastinal lymph nodes were swollen. Sarcoidosis was suspected but was ruled out by several tests. Laboratory examinations showed elevated inflammatory markers. Bone marrow examination showed the vacuolization of myeloid precursor cells. A skin biopsy revealed dense dermal, predominantly perivascular, infiltrates. These consisted of mature neutrophils admixed with myeloperoxidase-positive CD163-positive myeloid cells, lymphoid cells and eosinophils. Sequencing analysis identified the somatic UBA1 variant c.122T > C, which results in p.Met41Thr. Treatment with oral prednisone (15 mg/day) and monthly intravenous tocilizumab injections (400 mg) completely resolved the symptoms. Neutrophils are a major source of reactive oxygen species, and the present case demonstrated numerous neutrophilic infiltrates. We hypothesize that the patient might have had elevated derivatives of reactive oxygen metabolites (d-ROMs). d-ROM quantification is a simple method for detecting hydroperoxide levels, and clinical trials have proven it useful for evaluating oxidative stress. In this study, we measured serum d-ROM before and after oral prednisone and tocilizumab treatment. The levels decreased significantly during treatment.